Detecting Events in Molecular Dynamics Simulations - Adä, Iris; Berthold, Michael R. (My University, 2013)
We describe the application of a recently published general event detection framework, called EVE to the challenging task of molecular event detection, that is, the automatic detection of structural changes of a molecule over time. Di erent types of molecular events can be of interest which have, in the past, been addressed by specialized methods. The framework used here allows di erent types of molecular events to be systematically investigated. In this paper, we summarize existing molecular event detection methods and demonstrate how EVE can be con figured for a number of molecular event types.
Keywords: Event detection; Molecular Dynamics; 004